Religious Tolerance and Local Culture Acculturation in Realizing Sustainable Quality of Islamic Educational Institution - Nurcholiq, Mochamad; Mutholingah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2025)
The objective of this research was to formulate a multidisciplinary model for enhancing educational quality through these social-cultural dimensions. The research method was literature review, employing a multidisciplinary approach combining sociology, education and management theories with in-depth case studies, interviews and document analysis across selected institution. The result demonstrate a significant positive relation, institution fostering genuine tolerance and successful cultural acculturation exhibit superior, more sustainable quality indicators (lower conflict rates and higher community engagement). The discussion highlights that integration acts as non-governance mechanism that strengthens internal relationship. The conclusion was that a supportive, tolerant socio-culture environment is a prerequisite for long-term educational excellence. The novelty of this research that conceptually linking tolerance and acculturation as antecedents of sustainable quality. Theoretically, it expands the framework of educational management by incorporating socio-cultural factors. Practically,it suggest that institutional leaders should prioritize cultural intelligence and tolerance programs as essential quality assurance measures